Clinical Utility of CDK4/6 Inhibitors in Sarcoma: Successes and Future Challenges. (2nd February 2022) - Hsu, Jocelyn Y.; Seligson, Nathan D.; Hays, John L.; Miles, Wayne O.; Chen, James L.
Abstract : PURPOSE: Soft tissue and bone sarcomas are rare malignancies that exhibit significant pathologic and molecular heterogeneity. Deregulation of the CDKN2A-CCND-CDK4/6-retinoblastoma 1 (Rb) pathway is frequently observed in about 25% of unselected sarcomas and is pathognomonic for specific sarcoma subtypes. This genomic specificity has fueled the clinical evaluation of selective CDK4/6 inhibitors in sarcomas. Here, we highlight successes, opportunities, and future challenges for using CDK4/6 inhibitors to treat sarcoma. MATERIALS AND METHODS: This review summarizes the current evidence for the use of CDK4/6 inhibitors in sarcoma while identifying molecular rationale and predictive biomarkers that provide the foundation for targeting the CDK4/6 pathway in sarcoma. A systematic review was performed of articles indexed in the PubMed database and the National Institutes of Health Clinical Trials Registry (ClinicalTrials.gov). For each sarcoma subtype, we discuss the preclinical rationale, case reports, and available clinical trials data. RESULTS: Despite promising clinical outcomes in a subset of sarcomas, resistance to CDK4/6 inhibitors results in highly heterogeneous clinical outcomes. Current clinical data support the use of CDK4/6 inhibitors in subsets of sarcoma primarily driven by CDK4/6 deregulation. When dysregulation of the Rb pathway is a secondary driver of sarcoma, combination therapy with CDK4/6 inhibition may be an option. Developing strategies to identify responders and the mechanisms that drive resistance is important to maximize the clinical utility of these drugs in patients with sarcoma. Potential biomarkers that indicate CDK4/6 inhibitor sensitivity in sarcoma include CDK4, CCND, CCNE, RB1, E2F1, and CDKN2A . CONCLUSION: CDK4/6 inhibitors represent a major breakthrough for targeted cancer treatment. CDK4/6 inhibitor use in sarcoma has led to limited, but significant, early clinical success. Targeted future clinical research will be key to unlocking the potential of CDK4/6 inhibition in sarcoma. Abstract :